Outcomes of Mental Health Screening for United Kingdom Nationals Affected by the 2015–2016 Terrorist Attacks in Tunisia, Paris, and Brussels. Issue 4 (7th August 2018) - Gobin, Maya; Rubin, G. James; Albert, Idit; Beck, Alison; Danese, Andrea; Greenberg, Neil; Grey, Nick; Smith, Patrick; Oliver, Isabel
Abstract: Following several terrorist attacks in 2015 and 2016, a national program was set up to identify and support residents of England whose mental health had been affected. We report the outcomes of the program's screening and assessment components. Questionnaires and information about the program were mailed to 483 people and 49 families known to the police. Individuals who screened positive on an assessment for posttraumatic stress disorder, anxiety, depression, increased smoking, or problematic alcohol consumption were offered clinical assessment and referred to an appropriate National Health Service (NHS) service, if required. Of the 195 eligible people who returned our questionnaires, 179 (91.8%) screened positive on one or more measure. Following clinical assessment, 78 adults and three children were referred for treatment. The program was broadly successful in facilitating access to services. However, most people who had been directly exposed to the attacks did not participate and data protection issues limited communication with those who were affected. Further discussion of data protection concerns may help future programs operate more efficiently.